PROSPEK DESTINASI WISATA HALAL BERBASIS OVOP (ONE VILLAGE ONE PRODUCT) - M. ZAKY MUBARAK LUBIS (Maqdis: Jurnal Kajian Ekonomi Islam, 2018)
Indonesia is a rich and beautiful country to natural tourism destinations, one of which is the area of West Sumatra. West Sumatra belongs to the four categories of "Kompetisi Pariwisata Halal Nasional". West Sumatra has tremendous potential for the development of halal tourism sector, which will affect the economic growth of the community. The purpose of this paper is to know the prospects of halal tourism destinations in West Sumatra. The study is at Pagaruyung Palace. Review the concept of one village, one product. In this concept each region has and develops its own uniqueness that is not owned by other regions. With this difference will later add tourists who come. Through this concept in the future can create an independent society. West Sumatra can be used as a model or example for other areas in the management and development of halal tourism.